PROFIL MADRASAH TSANAWIYAH UNGGUL : MTs Negeri Winong, Kabupaten Pati, Jawa Tengah - Sumarni Sumarni (EDUKASI: Jurnal Penelitian Pendidikan Agama dan Keagamaan, 2015)
AbstractThis research aims at finding out how input, superiority and particularity of learning process, and output of MTs Negeri Winong Pati has influenced. The research on State Islamic Junior High School is Superior in adopting a qualitative descriptive method at MTs Negeri Winong Pati, Central Java. The research outcome shows that MTs Negeri Winong Pati has several superiorities and particularities. Of the input side, this school has qualified student input, adequate facility and infrastructure, professional teacher and supported by innovative management. The superiority and particularity owned by this school among others are history, physical particularity, financial independency, innovation on general and religious curriculum, learning innovation namely bilingual boarding school, olympic class, comparative overseas study and supported by innvovative learning method with IT. This school has a good achievement in terms of its institution, principal, teacher and student. The achievement is not only in academic  field but also non-academic and religious fields. AbstrakPenelitian ini bertujuan untuk mengetahui bagaimana input, keunggulan dan kekhasan proses pembelajaran, dan output MTs Negeri Winong Pati. Penelitian Madrasah Tsanawiyah Negeri Unggul menggunakan metode deskriptif kualitatif di MTs Negeri Winong Pati Jawa Tengah. Hasil penelitian menunjukkan bahwa MTs Negeri Winong Pati memiliki berbagai keunggulan dan kekhasan. Dari sisi input, madrasah ini memiliki input siswa yang berkualitas, sarana prasarana yang memadai, tenaga pengajar yang profesional, dan didukung manajemen inovatif. Keunggulan dan kekhasan yang dimiliki madrasah ini antara lain kesejarahan, kekhasan  fisik,  kemandirian pembiayaan, inovasi kurikulum umum dan agama, inovasi pembelajaran yaitu kelas bilingual boarding school, kelas olimpiade, studi banding keluar negeri, dan didukung metode pembelajaran inovatif dengan teknologi IT. Prestasi madrasah juga unggul baik prestasi lembaganya, kepala madrasah, guru, dan siswa. Prestasi tidak hanya di bidang akademik tetapi juga bidang non akademik dan keagamaan.